A call to ban the sale of tobacco products - Su, Zhaohui; McDonnell, Dean; Cheshmehzangi, Ali; Ahmad, Junaid; Šegalo, Sabina; da Veiga, Claudimar Pereira (Frontiers in Public Health, 2022)
Tobacco is both toxic and addictive. Mounting evidence shows that tobacco use has a detrimental impact on almost every aspect of human health, causing or worsening deadly public health crises from the cancer epidemic to the COVID-19 pandemic. However, while tobacco use is a threat to both personal and public health, it continues to surge across the world, especially in China and other low- and middle-income countries. To this end, this article argues in favor of using a ban on the sale of all tobacco products as a practical solution to the global tobacco use epidemic. It is our hope that insights provided by our work will inspire swift policy actions in countries such as China and beyond to curb the tide of rising tobacco consumption, so that populations around the world could be better shielded from the pervasive and long-lasting damage that tobacco products cause or compound.